1953
DOI: 10.1039/jr9530000623
|View full text |Cite
|
Sign up to set email alerts
|

126. Reactions of iodine pentafluoride with inorganic substances. Iodine oxytrifluoride and iodyl fluoride

Abstract: The reactions of iodine pentafluoride with typical oxides, salts, and metals are described. They lead to a number of new compounds many of which are of a molecular type. A straightforward method of preparing iodine oxytrifluoride is given and the reactions involved are made clear. Thermal decomposition of this compound gives rise to the new iodyl fluoride, I0,F; this can be reconverted into the oxytrifluoride by heating it with iodine pentafluoride. A study of some of these reactions and the physicochemical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1955
1955
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Those species which appear to be the best supported by previous studies are listed in Table I along with selected values for their formation quotients Qx.y = [AL(OHV3*-">-1 [H+U/W+U (1) Of these, A10H2+ has been reported by numerous investigators, many of whom4-9 have found reasonably (1) Research sponsored by the U. S. Atomic Energy Commission under contract with the Union Carbide Corp.…”
Section: Introductionmentioning
confidence: 90%
“…Those species which appear to be the best supported by previous studies are listed in Table I along with selected values for their formation quotients Qx.y = [AL(OHV3*-">-1 [H+U/W+U (1) Of these, A10H2+ has been reported by numerous investigators, many of whom4-9 have found reasonably (1) Research sponsored by the U. S. Atomic Energy Commission under contract with the Union Carbide Corp.…”
Section: Introductionmentioning
confidence: 90%
“…The principle of replacement by fluorine of oxygen acids and ions results in the existence of a number of other interesting fluorine compounds, such as C10 2 F, I0 2 F, I0 3 F, S0 2 F 2 , S 2 0 5 F 2 , S 2 0 6 F 2 , N0 2 F, Mn0 3 F, Cr0 2 F 2 , etc, (53,54,55,56).…”
Section: Perchloryl Fluoride and Other Fluorides Of The Oxy Acidsmentioning
confidence: 99%
“…(5) With some compounds, particularly terpenes, rearrangements of structure occur. (6) Chromium(VI) possesses tetrahedral coordination.…”
Section: Introduction and Historymentioning
confidence: 99%